Data from: The indicator side of tree microhabitats: a multi-taxon approach based on bats, birds and saproxylic beetles - Paillet, Yoan; Archaux, Frédéric; du Puy, Solène; Bouget, Christophe; Boulanger, Vincent; Debaive, Nicolas; Gilg, Olivier; Gosselin, Frédéric; Guilbert, Eric (Dryad, 2019)
1. National and international forest biodiversity assessments largely rely
on indirect indicators, based on elements of forest structure that are
used as surrogates for species diversity. These proxies are reputedly
easier and cheaper to assess than biodiversity. Tree microhabitats –
tree-borne singularities such as cavities, conks of fungi or bark
characteristics – have gained attention as potential forest biodiversity
indicators. However, as with most biodiversity indicators, there is a lack
of scientific evidence documenting their quantitative link with the
biodiversity they are supposed to assess. 2. We explored the link between
microhabitat indices and the richness and abundance of three taxonomic
groups: bats, birds, and saproxylic beetles. Using a nation-wide
multi-taxon sampling design in France, we compared 213 plots located
inside and outside strict forest reserves. We hypothesized that the
positive effect setting aside forest reserves has on biodiversity
conservation is indirectly due to an increase in the proportion of large
structural elements (e.g. living trees, standing and lying deadwood).
These, in turn, are likely to favour the quantity and diversity of
microhabitats. We analysed the relationship between the abundance and
species richness of different groups and guilds (e.g. red-listed species,
forest specialists, cavity dwellers) and microhabitat density and
diversity. We then used confirmatory structural equation models to assess
the direct and indirect effects of management abandonment, large
structural elements and microhabitats on the biodiversity of the target
species. 3. For several groups of birds and bats, the indirect effect of
management abandonment and large structural elements on biodiversity was
mediated by microhabitats. However, the magnitude of the link between
microhabitat indices and biodiversity was moderate. In particular,
saproxylic beetles’ biodiversity was poorly explained by microhabitats,
large structural elements or management abandonment. 4. Synthesis and
applications: Tree microhabitats may serve as indicators for bats and
birds, but they are not a universal biodiversity indicator. Rather,
compared to large structural elements, they most likely have a
complementary role to biodiversity. In terms of forest management and
conservation, preserving diversity of microhabitats at the local scale
benefits several groups of both bats and birds.
Data from Paillet te al. JAE 20182018-05-14.data.dryad.Paillet.JAE.xlsx
Keywords: indicator; strict forest reserve; structural equation models; tree-related microhabitats; cavities; saproxylic beetles